Conversion of lignin pyrolysis oil to cyclohexyl methyl ethers as a promising biomass-derived solvent. Issue 6 (12th March 2021) - Haseeb, Sohaib; Vanderveen, Jesse R.; Elamaldeniya, Devni; Harris, Jesse; Boniface, Kyle J.; Lee, Roland; Champagne, Pascale; Jessop, Philip G.
Abstract : A mixture of cyclohexyl methyl ethers was prepared from Kraft lignin pyrolysis oil for use as a biomass-derived aliphatic solvent. Abstract : A mixture of cyclohexyl methyl ethers was prepared from Kraft lignin pyrolysis oil for use as a biomass-derived aliphatic solvent. Using Kamlet–Taft solvatochromic parameters, it was determined that the solvent mixture is somewhat more basic and polar than cyclopentyl methyl ether. Neither the biomass-derived solvent nor pure cyclohexyl methyl ether formed any detectable peroxides in 12 weeks of exposure to air, even though THF formed peroxides rapidly under such conditions. This mixture can be used as a biomass-derived aliphatic ether solvent and as a potential replacement for THF, dioxane, ethyl acetate, acetone and 2-butanone.